Early Years Digital Portfolio - alina diaconu (22674974) (2025)
The Early Years Digital Portfolio (EYDP) project https://eydigifolio.ipb.pt/, developed under the Erasmus+ programme, aims to modernize early childhood education by introducing an innovative digital system that supports the documentation, evaluation, and communication of children’s learning and development. Through a dedicated online platform, educators can upload photos, observations, videos, and learning artifacts that reflect children’s progress, creating a structured and accessible portfolio for both teachers and families. This approach allows a clearer and more comprehensive understanding of each child’s growth, highlighting not only cognitive development but also emotional, social, and creative dimensions. The project brings significant advantages to educators, children, and parents alike. For educators, EYDP provides an efficient digital tool that reduces the time spent on traditional paperwork and offers a more coherent method for monitoring and evaluating learning. The platform enhances communication with families, allowing parents to follow children’s activities in real time and reinforcing their involvement in the educational process. All information is stored in an organized and secure environment, ensuring easy access and continuity in the documentation of each child’s journey. The impact of the EYDP project extends beyond daily classroom practice. It supports the digital transformation of early childhood education institutions, helping them align with contemporary European standards and promoting consistent, high-quality pedagogical practices. Teachers gain confidence in using digital resources and develop essential technological skills for the educational landscape of the future. Families become true partners in education through increased transparency and regular communication. At a broader level, the project contributes to building a culture of collaboration, innovation, and shared responsibility. By offering open resources, training materials, and a replicable model, EYDP has the potential to inspire wider educational reforms and to strengthen the overall quality of early childhood education across Europe.